2020
DOI: 10.1186/s40337-020-00343-y
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic abnormalities in 124 severely malnourished adult anorexia nervosa patients: frequency and relationship with body composition and biological features

Abstract: Background Anorexia Nervosa (AN) is a complex psychiatric disorder that can lead to specific somatic complications. Heart abnormalities are frequently reported, while their frequency and associated factors in severely malnourished AN patients remain poorly defined. Objectives This study aimed to characterize echocardiographic abnormalities in severely malnourished AN patients and to assess associated clinical, biological and related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Takotsubo cardiomyopathy can also be seen in patients with AN, and may be attributable to the stress of the psychological condition plus severe malnutrition. However, the cardiac ejection fraction is generally normal in people with AN; only 15% had a reduced ejection fraction in one reported series [ 42 ].…”
Section: Medical Complicationsmentioning
confidence: 99%
“…Takotsubo cardiomyopathy can also be seen in patients with AN, and may be attributable to the stress of the psychological condition plus severe malnutrition. However, the cardiac ejection fraction is generally normal in people with AN; only 15% had a reduced ejection fraction in one reported series [ 42 ].…”
Section: Medical Complicationsmentioning
confidence: 99%
“…Our understanding of cardiac structure and function in patients with AN continues to progress with comprehensive, modern, and dynamic echocardiographic evaluations and more recently cardiac MRI (CMRI) studies. A retrospective study evaluated Doppler echocardiograms in adult patients with AN with an average BMI of 12 (N = 124) [90]. All AN patients had subclinical cardiac impairments and 15% had reduced ejection fraction (EF).…”
Section: Cardiovascular Complications In Anorexia Nervosamentioning
confidence: 99%
“…Interestingly, AN-BP and hypertransaminasemia were independently associated with a reduced EF. Consideration for echocardiogram should be made in patients with AN (especially AN-BP) with hypertransaminasemia to prevent complications of heart failure with refeeding [90]. Doppler echocardiography used to assess aortic stiffness by pulse wave velocity in adolescent AN patients found increased arterial stiffness [91].…”
Section: Cardiovascular Complications In Anorexia Nervosamentioning
confidence: 99%
“…In an echocardiographic study of 124 severely malnourished adult patients with anorexia nervosa, Hanachi et al [ 12 ] found that subclinical myocardial impairment was common. In their study, 27% of participants had pericardial effusions and 15% had evidence of left ventricular systolic dysfunction, which was associated with elevated transaminases and a diagnosis of anorexia nervosa – binge eating purging type.…”
mentioning
confidence: 99%